Buletin Peternakan : Kebutuhan Kalsium Ayam Broiler Fase Starter dengan Penambahan Enzim Fitase - Eny Sholikhatin, Ferry Poernama, Nanung Danar Dono, Zuprizal (Peternakan UGM, 2016)
The aim of this study was to determine the calcium requirements of broiler chickens in starter phase with the addition of phytase enzyme. This experiment used 1,200 broiler chickens (mixed sex) for 21 days rearing period in a closed house. The basal diets was corn and soybean meal which contained 0.097% Ca and 0.123% P-av.